2010
DOI: 10.1179/136485910x12743554760225
|View full text |Cite
|
Sign up to set email alerts
|

Primary eye care in sub-Saharan African: do we have the evidence needed to scale up training and service delivery?

Abstract: The models for addressing the delivery of an eye-care service in sub-Saharan Africa have seen considerable revision in the last 30 years, and the on-going challenges, as well as the future needs, will probably require many more changes and new systems. There is a need to assess the different models that are currently employed, in order to ensure that all potential contributions to the elimination of avoidable blindness are used; the evolving concept of primary eye care (PEC) requires such assessment. For the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
60
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…A detailed review by Courtright et al [13] identified only five articles providing information on the effectiveness of general primary health care workers in practicing primary eye care. Steinkuller, in 1987, commented on the results of PEC training for general health care workers in South Africa, Tanzania, Kenya, and Malawi [14].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed review by Courtright et al [13] identified only five articles providing information on the effectiveness of general primary health care workers in practicing primary eye care. Steinkuller, in 1987, commented on the results of PEC training for general health care workers in South Africa, Tanzania, Kenya, and Malawi [14].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of this, there is persistent enthusiasm for the concept of providing eye services (diagnosis, treatment, and referral) at the most basic level of the health system by general PHCW in Africa [6]. PEC may be considered an example of “task shifting” from more specialized workers (dealing only with eye conditions) to less specialized.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of PEC became very popular with non-governmental organizations and it is frequently cited at meetings as a critical piece of the eye health services in developing countries. The lack of evidence for its benefits as practised, however, has been documented [6]. …”
Section: Introductionmentioning
confidence: 99%
“…In an effort to overcome this, primary eye care (PEC) as an integral part of primary health care (PHC) has been recommended as a key strategy. PEC means different things in different parts of the world [3]. In settings with more resources, “primary eye care” refers to services delivered by nurses and health assistants who are trained for and work more or less exclusively in eye care, such as ophthalmic clinical officers or ophthalmic nurses and assistants.…”
Section: Introductionmentioning
confidence: 99%